How Reliable and Valid Is the Student Autonomy Scale When Examined Through the Rasch Model? - Yuca, Verlanda; Suherman, Uman; Nurihsan, Juntika; Budiman, Nandang; Magistarina, Elrisfa (Universitas Negeri Padang, 2025)
Autonomy can influence students to regulate themselves through thinking, feeling, behaving, acting, being responsible for the decisions made and living them with social considerations. Several existing instruments for assessing student autonomy still contain items that are not yet relevant to the needs of Indonesian students. This presents an interesting opportunity to develop and adapt them to the diverse social, cultural, institutional, and academic backgrounds of Indonesian students, as well as the dynamics of diverse student populations. This study aims to develop a scale to validate student autonomy used purposive sampling. This study was conducted in 2024, involving 378 students as participants consisting of 39 males and 339 females aged 17-23 years at Padang State University. This instrument is called the Student Autonomy Scale. This study uses a quantitative approach with 40 questions with